2021
DOI: 10.1021/acssuschemeng.0c08793
|View full text |Cite
|
Sign up to set email alerts
|

Is Chitosan the Promising Candidate for Filler in Nature-Friendly Electrorheological Fluids?

Abstract: In this study, an electrorheological effect of the suspensions containing porous chitosan particles in olive oil in a wide range of electric fields is reported. Porous chitosan particles were produced by freeze-drying. The structure of the filler was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray scattering. Electrorheological behavior of low-filled fluids (0.1, 0.2, 0.5, and 1.0 wt %) was studied in shear and oscillation modes. Rheological data were fitted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…One of the proposed applications for cellulose particles is their utilization as a dispersed phase in electrorheological (ER) fluids [8][9][10], which are systems whose rheological behavior can be controlled via applied external electric fields [11]. While, in the absence of an electric field, electrically polarizable particles are randomly dispersed in continuous non-conducting medium and the fluid exhibits Newtonian behavior, in its presence, particles align to its direction creating rigid chain-like structures [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposed applications for cellulose particles is their utilization as a dispersed phase in electrorheological (ER) fluids [8][9][10], which are systems whose rheological behavior can be controlled via applied external electric fields [11]. While, in the absence of an electric field, electrically polarizable particles are randomly dispersed in continuous non-conducting medium and the fluid exhibits Newtonian behavior, in its presence, particles align to its direction creating rigid chain-like structures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Hao et al 9,10 successfully made an MoS 2 @SiO 2 -based ER fluid and an H 2 Ti 2 O 5 @MoS 2 @SiO 2 -based ER fluid in 2021. Kuznetsov et al 11,12 made a new ER fluid based on chitosan particles in 2021. Meanwhile, Dhar et al 13 used agarose to make an organic colloidal ER fluid, and Meng et al 14 successfully made ionic liquid-crystalline polysiloxane-based ER fluids.…”
Section: Introductionmentioning
confidence: 99%
“…47 The natural oils and fillers allow to create completely eco-friendly ERFs, [48][49][50] so polysaccharides are promising candidates from this point of view as well. 51,52 One of the ways to increase the electrorheological response is to change the electrophysical characteristics of the filler with surface modification or doping. [53][54][55] Several studies have shown that the incorporation of small inclusions into the structure of the filler leads to a change in the polarizability of the particles and optimization of the relaxation time, which significantly enhance the electrorheological response of fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such fluids show stable response in a wide temperature range which is of great importance for real practical application 47 . The natural oils and fillers allow to create completely eco‐friendly ERFs, 48–50 so polysaccharides are promising candidates from this point of view as well 51,52 …”
Section: Introductionmentioning
confidence: 99%